2017
DOI: 10.1016/j.visres.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Violations of Weber’s law tell us more about methodological challenges in sensorimotor research than about the neural correlates of visual behaviour

Abstract: The violation of Weber's law in grasping has been presented as evidence for the claim that grasping is guided by visual information which is distinct from the information used in perceptual tasks. Previously, we contested this claim and argued that biomechanical constraints of the hand might explain why Weber's law cannot be reliably uncovered in grasping movements. In a recent article Manzone and colleagues (2017) show that pantomime grasping follows Weber's law even with objects whose width is close to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…the visuomotor-channel framework, the absence of Weber's law requires an explanation. These have been provided in terms of biomechanical constraints Schenk et al 2017;Utz et al 2015) and in terms of the two-visual-systems hypothesis Ganel et al 2008;Heath et al 2017;Manzone et al 2017). Within the digit-in-space framework, no additional explanation is required.…”
Section: Additional Constraints and Grip Aperturementioning
confidence: 99%
“…the visuomotor-channel framework, the absence of Weber's law requires an explanation. These have been provided in terms of biomechanical constraints Schenk et al 2017;Utz et al 2015) and in terms of the two-visual-systems hypothesis Ganel et al 2008;Heath et al 2017;Manzone et al 2017). Within the digit-in-space framework, no additional explanation is required.…”
Section: Additional Constraints and Grip Aperturementioning
confidence: 99%
“…The value of the grip aperture in any given trial is likely to be the result of many factors: the estimated size of the object, the current noise in the motor system, and the intended approach angle to name just a few possible factors that can influence the maximum grip aperture. As we have argued elsewhere [23,24,32], it is in our view a mistake to treat the MGA as a perfect read-out of the motor system’s estimate of the target object’s size. Other constraints and sources of noise will contaminate this measure.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, Singhal et al [20] showed that a more general cognitive phenomenon, namely the finding that the concurrent execution of two tasks creates performance costs for at least one of the two tasks, reliably occurs in tasks that can be assigned to the perceptual system but is much less prominent in tasks assigned to the visuomotor system. However, all these approaches have been met with counter-evidence and are currently bogged down in controversy [21,22,23,24,25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, this very influential model has been criticized (Schenk, 2006(Schenk, , 2012Schenk, Franz, & Bruno, 2011;Schenk & Hesse, 2018) and many studies originially providing supporting evidence for segregated neurological pathways for perception and action processing (e.g., Aglioti, DeSouza, & Goodale, 1995;Ganel, Chajut, & Algom, 2008;Ganel & Goodale, 2003, 2014Goodale et al, 1994;Goodale & Milner, 1992) have been challenged (e.g., see Kopiske, Bruno, Hesse, Schenk, &Franz, 2016 for illusions, andSchenk et al, 2017;Utz, Hesse, Aschenneller, & Schenk, 2015 for Weber's law). However, there are two lines of evidence that have received comparably little scrutiny until now: The Garner Interference effect (Ganel & Goodale, 2003, 2014 and dual-task studies (Liu, Chua, & Enns, 2008;Singhal, Culham, Chinellato, & Goodale, 2007).…”
Section: Introductionmentioning
confidence: 99%